PERANCANGAN E-COMMERCE JUAL-BELI HASIL PETERNAKAN BERBASIS WEB - Nurhidayah Simbolon; Samsudin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The rapid development of information and communication technology today, including in the field of E-commerce, has had a significant impact on various sectors, including the livestock industry in rural areas. The livestock industry plays an important role in the local economy, and to increase the efficiency of the sale of livestock products, this study proposes the adoption of a web-based E-commerce system. This system is intended to replace traditional sales methods whose scope and effectiveness are limited. With E-commerce, farmers can market livestock products online, expand markets and increase income. On the consumer side, they can buy livestock products without having to go directly to the farm, helping to optimize time and labor efficiency. This study used an R&D (Research and Development) approach with interviews, observations and literature review. The development of the E-commerce system is carried out in a Waterfall approach to create a platform that provides objective information, supports the purchase and sale of livestock products quickly, efficiently and accurately. accurate, thereby bringing benefits to the seller and the buyer.